The Design of the Digital Direct Control (DDC) used in the Building Management System (BMS) (Latakia University Journal -Engineering Sciences Series, 2018)
In this paper, the work is based on the design of direct digital control circuits (DDC) which is one of the most important parts of the building management system (BMS) and the design of communication protocols necessary. This work has its importance from a technical point especially developed control software needed to design, in addition to the economic terms of providing these circuits through local manufacturing have not needed to be imported (which is not easy in most cases). The article described building management system and explains the most important components and focusing on the DDC circuits. The article presents the most important electronic components used in the design, where we used simulation software "Proteus" in circuit design, and for programming the controller we used the "Bascom AVR" program. In the end, we have implemented a direct digital control circuit with eight digital inputs and eight digital outputs. تصميم دارات التحكم الرقمي المُباشر(DDC) المُستخدمة في نظام إدارة المباني (BMS) يتمحور العمل في هذا البحث حول تصميم دارات التحكم الرقمي المُباشر(Digital Direct Control, DDC) والتي تُعتبر من أهم أجزاء نظام إدارة المباني Building Management System, BMS))وكذلك تصميم بروتوكولات الاتصال اللازمة لها. يتميز هذا العمل بأهميته التي تتمثل بالجانب الفني وخاصةً بوضع برامج المُتحكمات اللازمة للتصميم إضافة إلى الجانب الاقتصادي المُتمثل في توفير هذه الدارات من خلال التصنيع المحلي لها وعدم الحاجة لاستيرادها (والذي يكون غير سهل في معظم الأحيان). يوصّف البحث نظام ادارة المباني ويشرح أهم مكوناته مع التركيز على دارات الـ DDC. يستعرض البحث أهم في البداية ومن أجل تصميم دارات التحكم الرقمي المباشر قمنا باختيار العناصر الإلكترونية المُستخدمة في التصميم، حيث اعتمدنا على برنامج المحاكاة "Proteus" في التصميم الالكتروني للدارات،ومن أجل برمجة المُتحكم استخدمنا برنامج الـ "Bascom AVR". وفي النهاية،قمنا بتنفيذ دارة تحكم رقمي مُباشر ذات ثمانية مداخل رقمية وثمانية مخارج رقمية.